Effect Of Islamic Spiritual Interventions (Wudhu And Dhuha Prayer) On Anxiety Levels Of Medical Students Before Clinical Skills Examination - Ardi Artanto; Rury Tiara Oktariza; Hafiz Rifanza; Putri Zalika; Ridha Ilma (Jurnal Ilmu Kedokteran dan Kesehatan, 2026)
Anxiety is a physiological and emotional response to perceived threats, often experienced by medical students before exams such as the LKK exam. High levels of anxiety can negatively affect academic performance and mental well-being. Islamic psychotherapy techniques, such as wudhu (ablution) and dhuha prayer, are believed to have calming effects that reduce stress and anxiety. This study aims to analyze the effect of wudhu therapy and dhuha prayer on anxiety levels among medical students at Muhammadiyah University of Palembang before the LKK exam. This quasi-experimental study employed a pretest-posttest design without a control group. A total of 62 students meeting the inclusion and exclusion criteria were selected through simple random sampling. Anxiety levels were assessed using the Hamilton Anxiety Rating Scale (HARS) questionnaire. Data analysis was performed using the Wilcoxon test with a significance level of p 0.05. The study findings indicate a significant reduction in anxiety levels following the intervention, with a p-value of 0.05. Before the intervention, 87.1% of students exhibited moderate anxiety, while after the intervention, 91.9% of students reported mild anxiety. These results support the effectiveness of wudhu therapy and dhuha prayer as non-pharmacological interventions for reducing anxiety. The practice of wudhu and dhuha prayer significantly reduces anxiety levels in medical students before exams. These findings highlight the potential benefits of integrating Islamic psychotherapy into academic stress management strategies.